Additive Effects of Parent Adherence on Social and Behavioral Outcomes of a Collaborative School–Home Behavioral Intervention for ADHD - Villodas, Miguel T. (Child Psychiatry Hum Dev, 2014)
The present study evaluated the impact of the Collaborative Life Skills Program (CLS), a novel school–home psychosocial intervention, on social and behavioral impairments among children with attention and behavior problems. Fifty-seven ethnically/racially diverse children (70 % boys) with attention and/or behavior problems in the second through fifth grades participated in a pilot study. Ten school-based mental health professionals were trained and then implemented the intervention at their respective schools. Children significantly improved from pre- to post-treatment on parent, teacher, and report card ratings of children’s social and behavioral functioning. Treatment improvements were consistent for children with and without co-occurring disruptive behavior problems. The impact of the intervention was enhanced when parents used the intervention strategies more regularly, according to both clinicians’ and parents’ reports. Findings support the emphasis of CLS on coordinating intervention strategies across contexts to facilitate the generalization of treatment-related improvements in social and behavioral functioning.